Pengaruh Penerapan Standar Operasional Prosedur (SOP) dan Gaya Kepemimpinan Terhadap Kinerja Karyawan PT. Maju Kemuliaan Bersama Jaya - Anggia Shafira Selamet; Joseph M.J. Renwarin (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to examine the effect of the application of standard operating procedures (SOP) and leadership style on employee performance at PT. Maju Kemuliaan Bersama Jaya in sampling using non-probability sampling saturated, with the number of respondents as many as 55 employees. This study uses quantitative methods. The data collection method used a questionnaire. The analysis in this study uses classical assumption test and hypothesis test using multiple linear regression test, determination test, T test and F test with SPSS22 program. The results of this study indicate that, Leadership Style has a significant effect on employee performance. Meanwhile, the application of Standard Operating Procedures (SOP) and Leadership Style have a significant effect on employee performance.